Hermansky-Pudlak Syndrome: Spectrum in Oman. Issue 3 (21st April 2023) - Nazir, Hanan F.; AL Sukaiti, Nashat; Khater, Doaa; Elbeshlawy, Ismail; Hassanein, Nehad
Abstract : Hermansky-Pudlak syndrome (HPS) is a rare autosomal recessive disorder, characterized by oculocutaneous albinism, a hemorrhagic diathesis secondary to storage pool-deficient platelets, and in some patients' pulmonary fibrosis, granulomatous colitis, and immunodeficiency. To date, 11 different types of Hermansky-Pudlak syndrome were identified. HPS type 2 is distinctively characterized by severe neutropenia and recurrent sinopulmonary infections. HPS is more common in Puerto Rico, and this is the first report deciphering the genotypic spectrum of HPS in Oman. Between 2001 and 2021, 8 Omani cases with HPS (3 HPS type 2, 1 HPS type 3, and 4 HPS type 6) had been suspected clinically and confirmed through genetic mutation analysis. Patients had mild hemorrhagic phenotype, and variable platelet aggregation defects with different platelet agonists. All patients had characteristic eye manifestations. In addition, patients with HPS type 2 had severe neutropenia. Novel mutations in AP3B1(c.205-1G>C, c.12_13delTA (p.Asn4Lysfs*6) and HPS6 (c.19_20delCT (p. Leu7Alafs*168) were not reported in population variant databases. Diagnosis of HPS had markedly improved in Oman; however, increased clinician awareness is needed. A high index of suspicion and early referral for diagnosis and initiation of proper treatment might help improve outcomes.